REPOSISI KONSEP KETUHANAN: TANGGAPAN MUHAMMAD IQBAL DAN SAID NURSI ATAS PERJUMPAAN ISLAM DAN SAINS - M Maftukhin (IAIN Tulungagung, 2017)
Artikel ini menghadirkan dua cara pandang berbeda antara Muhammad Iqbal dan Said Nursi dalam upaya reposisi konsep ketuhanan saat Islam bertemu sains. Artikel ini memperlihatkan bagaimana Iqbal menerima sains dengan melakukan penyesuaian ajaran Islam agar sejalan dengan epistemologi sains dan rasionalisme dengan tetap merujuk pada al-Qur’an. Konsep ketuhanan teis yang dirasa tidak sesuai dengan rasionalisme dan perkembangan sains, mendapat sentuhan Iqbal dengan dikonstruksi menjadi konsep panentheisme. Sementara itu, Said Nursi, meskipun ia juga mendorong adopsi sains, namun Nursi hampir tidak melakukan penyesuaian apa pun dalam konsep ketuhanan Islam. Sebagai pewaris pemikiran al-Asy’ariyyah, justru Nursi memilah sains dalam dua kategori, yaitu sains yang memuat nilai positif dan sains yang memuat aspek negatif. Selanjutnya Nursi hanya mengambil aspek positif dan meninggalkan aspek negatifnya. Dengan menggunakan teori Ian Barbour, artikel ini memasukkan pendekatan Iqbal dalam kategori integrasi epistemologis, sedangkan pendekatan Said Nursi masuk dalam kategori integrasi ontologis.This article seeks to presents a distinct view of two Muslim thinkers on repositioning concept of God in the face of adoption to science. That is of Muhammad Iqbal’s and of Said Nursi’s. It shows that Iqbal used methods of reconstruction on Islamic theology in order for which go in line with scientific epistemology despite it remains strongly based on the Qur’an. Iqbal is of the view that theistic God of Islam appears to come in contrast to the rationalism and modern scientific approaches. For that reason, Iqbal changed this theistic God to be a panentheistic God of modern sciences. On the other side, Said Nursi urges Muslim community to adopt science as well, but—in contrast to Iqbal—he did almost nothing in reconstructing Islamic theology. As in heritor of the doctrines of Ash’arite, instead he classified modern science into two camps, that of the positive in term of Islamic interests and that of the negative. He adopts the positive one while keeping at bay the rest. Departing from Ian Barbour’s theory, this article categorizes Iqbal’s and Nursi’s adoption to science as integration. This article proposes that the method of Iqbal’s integration during his reconstruction on Islamic theology is an epistemological integration, meanwhile Nursi’s approach is ontological integration.